Bicervical Normal Uterus with Normal Vagina and Anteroposterior Disposition of the Double Cervix - José Morales-Roselló; Núria Peralta LLorens (Case Reports in Medicine)
We report a very uncommon uterine anomaly consisting on a normal uterus, a double cervix with an anteroposterior disposition, and absence of vaginal septum. A 36-years-old woman with one child and absence of past reproductive disorders was examined for a routine checkup. Clinical and transvaginal ultrasound examinations showed a normal uterus with a double cervix disposed in an anteroposterior fashion with the absence of vaginal septum. A review of the theories concerning müllerian fusion is done, and implications of this case in relation with these theories are discussed. This is the first case of a normal uterus with a double cervix situated in an anteroposterior fashion and absence of vaginal septum. This case is in concordance with theories that consider the fusion of the caudal part of Müllerian ducts to be the result of a complex process. It proves that at least in some cases the most caudal part of müllerian ducts is fused in an anteroposterior disposition.